Effect of raised serum uric acid level on perinatal and maternal outcome in cases of pregnancy-induced hypertension (Bangabandhu Sheikh Mujib Medical University Journal, 2017)
The aim of this study was to find out the effects of raised serum uric acid level on perinatal and maternal outcome in cases of pregnancy-induced hypertension. One hundred pregnant women with gestational period beyond 28 weeks with pregnancy-induced hypertension-preeclampsia and eclampsia were included in this study and divided into two groups. Group A (n=65) patients with a serum uric acid level >6 mg/dL was compared to Group B (n=35) patients with a uric acid level